Penguatan Kurikulum Merdeka Berbasis Deep Learning melalui Kegiatan Kokurikuler pada Materi Kegiatan Ekonomi di SMA Negeri 6 Surakarta (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
. This study examines the strengthening of the Independent Curriculum based on Deep Learning through co-curricular activities on the topic of Economic Activities at SMA Negeri 6 Surakarta. This research is motivated by the finding that deep learning–oriented instruction has been implemented in Economics classroom learning; however, co-curricular components have not yet been optimally integrated to support holistic learning experiences. Using a descriptive qualitative approach, data were collected through systematic observation, in-depth interviews, and documentation. The participants involved one Economics teacher, six Grade 10 students, and several micro, small, and medium enterprises (MSMEs) located around the school environment. The findings reveal that co-curricular field study activities enable students to directly connect theoretical concepts of production, distribution, and consumption with authentic real-world economic practices. As a result, learning becomes more mindful, meaningful, and enjoyable for students. Furthermore, these activities significantly enhance students’ analytical thinking skills, learning engagement, motivation, and understanding of local economic dynamics. Therefore, the integration of co-curricular activities plays an important role in strengthening the implementation of the Independent Curriculum based on Deep Learning.